Habitação e centros históricos: a importância da política integrada para a reabilitação dos centros urbanos: os casos de Salvador e do Porto - Sousa, António Miguel Lopes de (2015)
This thesis intended to be developed by the present research, maintains that Housing, understood as integrated public policy, constitutes a determining component in the process of regeneration of the central areas in the cities, namely the historic centers. It proposes the study, through the analysis of paradigmatic cases of intervention in historic centers of cities in Brazil and Portugal i.e. Salvador and Porto the sets of constraints which allow the structuring of programs or continuing public politics, from which there were significant results in the process of rehabilitation and preservation of these centers. It is important, in regards to the present research, to put into context, not only the programmatic formulas but, and, especially, the conceptual foundations associated with them, in a way to understand the relevance of urban planning practices which are part of the housing issue and verify the forms of articulation and the respective impacts in the process of sociability and functional revitalization of the historic centers. Thus, by document analysis and by empirical observation of a set of experiments, which proceeded the configuration of housing policies for the historic centers studied, it is the intention to evaluate which transformations and concept development from which resulted significant contributions for the formulation of urban policies on handling housing shortages, typical of these and other centers. On the other hand, it is important to verify the circumstances in which the referred practices have not occurred, where the historical process demonstrates maladjustment or non-completion of the programmatic assumptions